Chromosome-scale Echinococcus granulosus (genotype G1) genome reveals the Eg95 gene family and conservation of the EG95-vaccine molecule - Korhonen, Pasi K.; Kinkar, Liina; Young, Neil D.; Cai, Huimin; Lightowlers, Marshall W.; Gauci, Charles; Gasser, Robin B. (Nature Portfolio, 2022)
Cystic echinococcosis is a socioeconomically important parasitic disease caused by the larval stage of the canid tapeworm Echinococcus granulosus, afflicting millions of humans and animals worldwide. The development of a vaccine (called EG95) has been the most notable translational advance in the fight against this disease in animals. However, almost nothing is known about the genomic organisation/location of the family of genes encoding EG95 and related molecules, the extent of their conservation or their functions. The lack of a complete reference genome for E. granulosus genotype G1 has been a major obstacle to addressing these areas. Here, we assembled a chromosomal-scale genome for this genotype by scaffolding to a high quality genome for the congener E. multilocularis, localised Eg95 gene family members in this genome, and evaluated the conservation of the EG95 vaccine molecule. These results have marked implications for future explorations of aspects such as developmentally-regulated gene transcription/expression (using replicate samples) for all E. granulosus stages; structural and functional roles of non-coding genome regions; molecular 'cross-talk' between oncosphere and the immune system; and defining the precise function(s) of EG95. Applied aspects should include developing improved tools for the diagnosis and chemotherapy of cystic echinococcosis of humans. A high-quality genome for the parasitic tapeworm, Echinococcus granulosus, provides further insight into the EG95 vaccine target for cystic echinococcosis.
Keywords: De-Novo Identification; Vaccine Antigen; Rna; Annotation; Generation; Sequences; Alignment; Platform; Reconstruction; Integration